Measles neutralising antibody levels in patients receiving intravenous immunoglobulin treatment - a sub-analysis of a randomized, cross-over bioequivalence trial. - Vatsala Rajendram; Martyn Paddick; John More (PLoS ONE)
Background Intravenous immunoglobulin is a replacement therapy for patients living with primary immunodeficiencies. Each batch of intravenous immunoglobulin is required by the Food and Drug Administration to contain threshold levels of measles neutralising antibodies. Widespread use of the measles vaccine has decreased measles antibody potency in the United States plasma supply. There is limited data on measles antibody trough levels in treated primary immunodeficiency patients. The aim of this sub-analysis was to evaluate the measles antibody trough levels in treated primary immunodeficiency patients. Methods GMX07 was an open-label, two-period, crossover bioequivalence study which randomized 33 adult patients with primary immunodeficiency disease in 16 centres across the United States, the United Kingdom and Hungary. Eligible adult patients received five infusions of Gammaplex® 5% followed by five infusions of Gammaplex® 10%, or vice versa, on either a 21- or 28-day dosing regimen. The trial included 15 paediatric patients who were not randomized, receiving only five infusions of 10% product. This sub-analysis measured trough levels of measles neutralising antibodies using a Vero cell-based measles virus neutralisation assay. Results Median measles antibody trough levels were ~ 1300 mIU/mL with no significant difference between Gammaplex 5% and Gammaplex 10% treatment (p >  0.9) or the 21-day or 28-day dosing regimen (p >  0.3). There was also no difference between mean measles neutralising antibody levels following Gammaplex 10% in adult or paediatric patients. Conclusions Levels of measles neutralising antibodies in the 5% and 10% formulations of this intravenous immunoglobulin product provided protective antibodies well above accepted thresholds and were similar in adult and paediatric patients across both 21-day and 28-day dosing regimens. Switching between Gammaplex products did not affect antibody levels. Trial registration ClinicalTrials.gov NCT01963143.